2015
DOI: 10.1155/2015/324841
|View full text |Cite
|
Sign up to set email alerts
|

Ranibizumab for Visual Impairment due to Diabetic Macular Edema: Real-World Evidence in the Italian Population (PRIDE Study)

Abstract: Purpose. An expanded access program (PRIDE study) in Italy to provide ranibizumab 0.5 mg to diabetic macular edema (DME) patients, prior to reimbursement. Methods. Open-label, prospective, phase IIIb study. Majority of patients were not treatment-naïve before enrollment. Patients received ranibizumab as per the EU label (2011). Safety was assessed by incidences of ocular/systemic adverse events (AEs) and serious AEs (SAEs) and efficacy in terms of visual acuity (VA) change from baseline (decimal score or Snell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…This is quite disappointing compared with the pivotal trials,2 3 5–7 9 13–15 which observed a mean gain of 10.6–11.1 letters at 12 months. DMO observations from smaller open-label prospective, phase IIIb studies such as PRIDE (Efficacy and Safety of Ranibizumab Alone or in Combination With Laser Photocoagulation vs. Laser Photocoagulation Alone in Proliferative Diabetic Retinopathy) (n=515), RELIGHT (Ranibizumab Treatment of Diabetic Macular Oedema With Bimonthly Monitoring After a Phase of Initial Treatment) (n=108) and RETAIN (Long-term Outcomes in Patients with Retinal Vein Occlusion Treated with Ranibizumab) (n=332) observed slightly greater VA acuity gains at >12 months ranging from four to eight letters 16 17. However, the gain at 12 months is similar to real-world studies16 18 and within the range from an analysis of several trials 19…”
Section: Discussionmentioning
confidence: 99%
“…This is quite disappointing compared with the pivotal trials,2 3 5–7 9 13–15 which observed a mean gain of 10.6–11.1 letters at 12 months. DMO observations from smaller open-label prospective, phase IIIb studies such as PRIDE (Efficacy and Safety of Ranibizumab Alone or in Combination With Laser Photocoagulation vs. Laser Photocoagulation Alone in Proliferative Diabetic Retinopathy) (n=515), RELIGHT (Ranibizumab Treatment of Diabetic Macular Oedema With Bimonthly Monitoring After a Phase of Initial Treatment) (n=108) and RETAIN (Long-term Outcomes in Patients with Retinal Vein Occlusion Treated with Ranibizumab) (n=332) observed slightly greater VA acuity gains at >12 months ranging from four to eight letters 16 17. However, the gain at 12 months is similar to real-world studies16 18 and within the range from an analysis of several trials 19…”
Section: Discussionmentioning
confidence: 99%
“…propose that due to higher APTC event rates found in ranibizumab, that such events should also be monitored in future. 12 A recent systematic review and meta-analysis of prolonged monthly anti-VEGF use in DME, the assessment of the highest-level exposure group (patients receiving monthly treatment over two years) revealed a possibly increased risk for death and potentially for cerebrovascular accidents. Therefore, the authors concluded that total exposure to anti-VEGF drugs in patients at high risk for vascular diseases should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of choroidal neovascularization is a common complication of macular laser treatments. The use of macular photocoagulation has become questionable since observing the promising outcomes of the use of anti-VEGF agents in visual and anatomical outcomes in the treatment of DME and their effectiveness in slowing the progression of diabetic retinopathy (4)(5)(6)(7)(8)(9). In particular, the risk of enlarging scars might be an important disadvantage in the subgroup of patients with DME but a better VA.…”
Section: Discussionmentioning
confidence: 99%
“…Ranibizumab has been proven to be effective in various DME treatment regimens that were monthly, pro re nata (PRN), treat and extend, etc. (4)(5)(6)(7)(8)(9)(10). In pivotal multicenter studies, it has been demonstrated that in the first 12 months of treatment, a mean of 8 to 9 ranibizumab injections was required; however, the mean injection number dramatically decreased after the first year (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation